Representasi Maskulinitas Modern Laki-laki Jepang dalam Film Perfect World Berdasarkan Semiotika Barthes - Fajria Noviana (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Abstract: This paper aims to provide an overview of the concept of masculinity in Japanese society today which is represented by the main character in “Perfect World” film. The concept of masculinity here is limited to the masculinity of the male main character with a disability, considering that people with disabilities are often seen and treated as second-class citizens by the surrounding community. The method used is the semiotic method of Barthes, because it not only provides an interpretation of a sign into language, but also sees signs from the ideological side of a culture. Furthermore, Chafetz's concept of masculinity is also used as a reference for assessing the masculinity of the main character. As a result, it was found that a man with disability can still be said to be masculine, whether in traditional or modern concepts. In addition, it can be said that the impermanence of the concept of masculinity is greatly influenced by time and the supporting society in which the concept was born. Men with disabilities can still be said to be masculine, as long as most of his masculinity assessment points are still fulfilled. On the other hand, a man without physical limitations can be said to be non-masculine if he cannot meet his masculinity assessment points.Keywords: gender, semiotics, masculinity, difabel, Barthes